Passive blockholders, informational efficiency of prices, and firm value. Issue 3 (23rd October 2019) - Chung, Kee H.; Lee, Choonsik; Shen, Carl Hsin‐han
Abstract: This paper analyzes the role of passive blockholders in corporate governance using data on Schedule 13G filings. We show that firm value increases with the number and aggregate ownership of passive blockholders after controlling for other possible determinants of firm value. More importantly, we show that the informational efficiency of prices (IEP) increases with the number and aggregate ownership of passive blockholders, and IEP is a channel through which passive blockholders affect firm value. Overall, our results suggest that managers perform better when stock prices reflect the economic consequences of their actions promptly and accurately through information‐based trading of blockholders.